The Challenges of Teaching Ambulatory Internal Medicine: Faculty Recruitment, Retention, and Development: An AAIM/SGIM Position Paper - Fazio, Sara B.; Chheda, Shobhina; Hingle, Susan; Lo, Margaret C.; Meade, Lauren; Blanchard, Melvin; Hoellein, Andrew; Brandenburg, Suzanne; Denton, G. Dodd (The American journal of medicine, 2017)
Difficulty in recruiting and retaining clinical faculty to teach learners is widely reported. Data from the 2010 Association of Program Directors in Internal Medicine survey demonstrate that greater than 40% of programs reported difficulty recruiting core ambulatory faculty and training them in competency-based assessment. Ambulatory faculty members are subject to multiple competing interests, including clinical access needs, administrative and financial requirements, and time limitations. Mechanisms to recruit and retain talented faculty to teach and mentor learners, including the provision of salary support, job security, academic advancement, and ongoing faculty development, must be addressed. Here, Fazio et al discuss how to engage and support talented faculty in ambulatory education.